A New Level In Medical Education: Epa – An Innovative Pedagogical Approach To Teaching The Subject “Information Technologies In Medicine” (Progress Annals: Journal of Progressive Research, 2025)
Contemporary medical education demands not only the acquisition of theoretical knowledge but also the development of advanced practical skills among students. In this context, the teaching of subjects such as “Information Technologies in Medicine” plays a critical role, as it equips future healthcare professionals with the ability to navigate and utilize medical informatics and digital health systems effectively. There is an increasing necessity to prepare students not just as passive learners but as independent, responsible, and digitally competent medical specialists